Mainstreaming Strategies of Religious Moderation in Madrasah - Miftahur Rohman; Muhammad Akmansyah; Mukhibat Mukhibat (AL-TAHRIR, 2022)
The mainstreaming of the values of religious moderation has been carried out by madrasas in Indonesia long before it became a priority program of the Ministry of Religion which was initiated by the former Minister of Religion, Lukman Hakim Syaifuddin. MA Bustanul 'Ulum and MA Roudlotul Huda Central Lampung are Islamic educational institutions that are pretty old in Central Lampung, which seem to have some uniqueness from the education system that contains efforts sow the values of religious moderation. Therefore, using a purposive sampling technique, researchers are interested in conducting research in both madrasas, which aims to identify the characteristics of the madrasa curriculum, analyze the leadership role of the madrasa principal, and find out the teacher's example in internalizing the values of religious moderation in madrasas. Research data were collected through observation, in-depth interviews, and documentation techniques which were then analyzed using Miles and Hubberman qualitative analysis: data reduction, data presentation, and verification. The study results conclude that the curriculum's characteristics are integrated curriculum with Islamic boarding schools that are implemented with a socio-religious approach, apply multicultural leadership, and exemplify intra-religious cultural dialogue with students. This qualitative research ultimately has limitations considering that the results of this study do not reflect the characteristics of madrasas in general. Therefore, it is necessary to conduct more comprehensive research to determine the mainstreaming of religious moderation values in madrasas.